Impact of baleen whales on ocean primary production across space and time - Carla Freitas; Morten D. Skogen; Guðjón M. Sigurðsson; Martin Biuw; Tore Haug; Lotta Lindblom; Kjell Gundersen (Proceedings of the National Academy of Sciences, 2025)
Primary production in the ocean is a fundamental process that supports marine food webs and global carbon sequestration. This process depends on nutrients that are often limited in surface waters. Whales are known to release essential elements such as nitrogen, phosphorus, and iron, yet the extent of their contribution to ocean primary production remains unclear. Here, we present daily estimates of nutrient input by baleen whales in high-latitude feeding grounds (Nordic and Barents Seas), based on multielement analyses of feces and urine. We then used end-to-end ecosystem models to assess the impact of these nutrients on primary production. We found that nitrogen is primarily excreted via urine, whereas phosphorus and trace elements are mainly released through feces. Ecosystem models indicate that baleen whales, including minke, fin, sei, humpback, blue, and bowhead whales, support annual and seasonal net primary production, with varying impacts across space and time. While the annual effects are modest (<2%) in most areas, the greatest impacts (up to 10%) occur during summer stratification and in offshore areas far from other nutrient sources. These increases in primary production have cascading effects on the food web, driving rises in mesozooplankton biomass. This study highlights the ecological significance of nutrient cycling by whales and underscores the value of integrating whale nutrient data into ecosystem modeling to assess the broader impacts of whales on marine productivity.